2022
DOI: 10.1080/19490976.2022.2156255
|View full text |Cite
|
Sign up to set email alerts
|

Intratumor microbiome features reveal antitumor potentials of intrahepatic cholangiocarcinoma

Abstract: Intrahepatic cholangiocarcinoma (ICC) is a rare malignancy with a high prevalence in China. This study aimed to characterize the ICC tissues’ bacterial metagenomics signature and explore its antitumor potential for cancer. In this study, 16S rRNA sequencing was carried out on 99 tissues to characterize the features of intratumoral microbiota, followed by single-cell RNA sequencing (scRNA-seq) and multilevel validation. The presence of microbial DNA in tissues was determined using staining, fluorescence in situ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 60 publications
0
28
0
1
Order By: Relevance
“…Some bacterial species have antitumour activity against tumours, such as Paraburkholderia fungorum, which inhibits tumour growth mainly through the regulation of alanine, aspartate and glutamate metabolism. 27 In contrast, the intestinal estrogen receptor beta can impede the progression of CRC by mediating the formation of beneficial microbiota. 31 Microbiome dysbiosis contributes significantly to carcinogenesis on a number of levels, including immunological, inflammatory and metabolic pathways.…”
Section: Microorganisms Can Influence the Growth And Proliferation Of...mentioning
confidence: 99%
See 1 more Smart Citation
“…Some bacterial species have antitumour activity against tumours, such as Paraburkholderia fungorum, which inhibits tumour growth mainly through the regulation of alanine, aspartate and glutamate metabolism. 27 In contrast, the intestinal estrogen receptor beta can impede the progression of CRC by mediating the formation of beneficial microbiota. 31 Microbiome dysbiosis contributes significantly to carcinogenesis on a number of levels, including immunological, inflammatory and metabolic pathways.…”
Section: Microorganisms Can Influence the Growth And Proliferation Of...mentioning
confidence: 99%
“…It has been indicated that the microbial composition is generally similar between tumours and adjacent tissues, possibly suggesting the temporal and spatial features of microbial ecosystems. 27,28 Cancer cells infected by bacteria are able to invade the surrounding area as a single cell and can also attract myeloid cells to the bacterial region. 3 The recruitment of myeloid cells can be observed in GC.…”
Section: Microorganisms Can Influence the Growth And Proliferation Of...mentioning
confidence: 99%
“…The intratumor microbiome can also modulate the tumor biology via influencing metabolism. In intrahepatic cholangiocarcinoma, the intratumor microbiota Paraburkholderia fungorum was significantly enriched in paracancerous tissues, which could inhibit tumor growth through alanine, aspartate, and glutamate metabolism 91 . And in breast cancer, integrating bulk and single‐cell RNA sequencing data revealed that the intratumor microbiome was significantly associated with metabolic heterogeneity in breast cancers, highlighting the need for further mechanistic investigations 92 .…”
Section: Mechanisms Of Intratumor Microbiome In Modulating Tumor Init...mentioning
confidence: 99%
“…CRC tissues are notable for their higher bacterial and fungal load in comparison to healthy tissue, with particular bacterial strains enriched within the tumor. 22 The intratumoral microbiota in CRC can be attributed to three primary sources. 23,24 First, the mucosal barrier of the colon, which naturally houses diverse microorganisms, becomes a conduit for these microbes during instances of mucosal damage caused by tumor development.…”
Section: Intratumoral Microbiota An Integral and Indispensable Compon...mentioning
confidence: 99%
“…CRC tissues are notable for their higher bacterial and fungal load in comparison to healthy tissue, with particular bacterial strains enriched within the tumor 22 …”
Section: Intratumoral Microbiota An Integral and Indispensable Compon...mentioning
confidence: 99%